2013
DOI: 10.1111/ter.12043
|View full text |Cite
|
Sign up to set email alerts
|

The South American ancestry of the North Patagonian Massif: geochronological evidence for an autochthonous origin?

Abstract: New U‐Pb and 40Ar/39Ar age data from deformed and undeformed granitoids of the North Patagonian Massif establish the presence of Early Cambrian and widespread Ordovician magmatism in northern Patagonia. These data suggest that the Pampean (Cambrian) and Famatinian (Ordovician) magmatic belts of the Sierras Pampeanas are continuous into Patagonia. SHRIMP U‐Pb age spectra from detrital zircons of Cambro‐Ordovician metasedimentary rocks show patterns very similar to those from equivalent units of the Pampia block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0
24

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(135 citation statements)
references
References 21 publications
(41 reference statements)
6
105
0
24
Order By: Relevance
“…The present study was initially undertaken to re-collect and date samples from the same critical localities. Meanwhile, the first U-Pb SHRIMP ages on zircon to be carried out in this area have been published: Chernicoff et al (2013) obtained a new age of 261 ± 3 Ma for zircon from granite from the western part of the Yaminué complex, and Rapalini et al (2013) have reported an Ordovician age of 467 ± 7 Ma for the southernmost sector of the complex and a Cambrian age of 529 ± 4 Ma for the Tardugno Granodiorite. These widely differing ages emphasize the need for more comprehensive study incorporating geochronology, geochemistry and isotope data to characterize the evolution and nature of Yaminué/Tardugno magmatism, which we have attempted to address here.…”
Section: Magmatism Subduction and Collision In Northern Patagoniamentioning
confidence: 99%
See 3 more Smart Citations
“…The present study was initially undertaken to re-collect and date samples from the same critical localities. Meanwhile, the first U-Pb SHRIMP ages on zircon to be carried out in this area have been published: Chernicoff et al (2013) obtained a new age of 261 ± 3 Ma for zircon from granite from the western part of the Yaminué complex, and Rapalini et al (2013) have reported an Ordovician age of 467 ± 7 Ma for the southernmost sector of the complex and a Cambrian age of 529 ± 4 Ma for the Tardugno Granodiorite. These widely differing ages emphasize the need for more comprehensive study incorporating geochronology, geochemistry and isotope data to characterize the evolution and nature of Yaminué/Tardugno magmatism, which we have attempted to address here.…”
Section: Magmatism Subduction and Collision In Northern Patagoniamentioning
confidence: 99%
“…K-Ar and Ar-Ar cooling ages for the Valcheta granites fall in the interval 470-430 Ma (López de Luchi et al 2008;Tohver et al 2008;Gozalvez 2009;Rapalini et al 2013). The oldest ages correspond to the more central parts of the pluton whereas the youngest cooling age (430 ± 6 Ma) was obtained from a pink aplo-pegmatitic monzogranite dyke located close to the eastern contact (Rapalini et al 2013).…”
Section: The Valcheta Plutonmentioning
confidence: 99%
See 2 more Smart Citations
“…There are widespread exposures of Late Carboniferous to Permian granitoids that intrude Cambrian-Ordovician metamorphic rocks (López de Lucchi et al, 2010;Martínez Dopico et al, 2011). In the area west of Sierra Grande there are highly deformed porphyritic granodiorite-biotite monzogranites, as the Tardugno Granodiorite, which in its type locality yields an age of 528.5 ± 3.5 Ma (U-Pb SHRIMP data, Rapalini et al, 2013). The metaclastic units of the Nahuel Niyeu Formation with some levels of metavolcanic rocks broadly related with an active margin environment yields detrital zircons older than 515 Ma (Pankhurst et al, 2006) for the lower grade rocks near Puesto Naverrete (Fig.…”
Section: Pre-silurian Geology Of Patagoniamentioning
confidence: 99%